Partisipasi Perseroan Terbatas: Corporate Social Responsibility and Environmental Management - Nurhikmah Nurhikmah; Budi Setiawati; Muhammad Randhy Akbar (Department of Public Administration, Muhammadiyah University of Makassar, 2024)
The company's obligation in Corporate Social Responsibility (CSR) is an important part of the social and environmental responsibility that must be fulfilled by the company. Companies have an obligation to contribute to the development of communities around their areas of operation. This can include education programmes, local economic empowerment, skills training, infrastructure development, and charitable activities. This research aims to analyse the role of limited companies related to Corporate Social Responsibility in improving the corporate image of PT Kawasan Industri Makassar on social and environmental aspects. The type of research used is qualitative research with data collection methods used in this research through interviews, observation, and documentation. The results showed that, the implementation of KIMA Green Corporate Social Responsibility through the greening movement programme and infiltration wells carried out by the company PT Kawasan Industri Makassar has shown the company's commitment to the environment and its social responsibility and is able to provide benefits to the community around the implementation location, as well as build better relationships between the company and the community, so that this programme can improve a good image for the company.